Small Cell Carcinoma of Cervix: Case Report of Rare Cervical Cancer Subtype (Nepalese Journal of Radiology, 2025)
Small cell carcinoma of the cervix is a rare and aggressive type of cancer that presents with early metastasis and poor prognosis. There are no specific features on imaging to distinguish it from the more common types, like squamous cell carcinoma. As the management differs from common subtypes, proper identification is essential for better prognosis. We present a case of a 42-year-old female with small cell carcinoma of the cervix with parametrial spread, vaginal involvement, and metastatic iliac lymphadenopathy. She was treated with sequential chemotherapy and radiation as per standard guidelines.